Cash Transfers, Behavioral Changes, and Cognitive Development in Early Childhood : Evidence from a Randomized Experiment - Macours, Karen; Schady, Norbert; Vakis, Renos (American Economic Association, 2014)
Cash transfer programs have become extremely popular in the developing world. A large literature analyzes their effects on schooling, health and nutrition, but relatively little is known about possible impacts on child development. This paper analyzes the impact of a cash transfer program on early childhood cognitive development. Children in households randomly assigned to receive benefits had significantly higher levels of development nine months after the program began. There is no fade-out of program effects two years after the program ended. Additional random variation shows that these impacts are unlikely to result from the cash component of the program alone.